Polytetrafluoroethylene (PTFE) hollow fiber AnMBR performance in the treatment of organic wastewater with varying salinity and membrane cleaning behavior. (November 2018) - Li, Jing; Jiang, Changwang; Shi, Wansheng; Song, Feiyue; He, Di; Miao, Hengfeng; wang, Tao; Deng, Jingxuan; Ruan, Wenquan
Highlights: PTFE hollow fiber AnMBR treats Saline wastewater COD removal rate over 97.2%. Salinity affected membrane filtration performances and fouling character. LMW of carbohydrates play an important role on membrane fouling. Over 91.6% of membrane flux could be recovered with offline cleaning procedure. PTFE hollow fiber AnMBR is an effective method to treat saline organic wastewater. Abstract: PTFE hollow fiber anaerobic membrane bio-reactor (AnMBR) performance was investigated in the treatment of organic wastewater, with varying salinity and PTFE membrane cleaning behavior. The AnMBR was operated for 226 days, with a total and biological COD removal efficiency of 97.2% and 89.9% respectively, at a NaCl concentration of 35 g L −1 . A high number of Proteobacteria (38.2%) and Bacteroidetes (25.9%) were present in the system, with an increase in membrane fouling rate from 1.88 × 10 11 to 2.63 × 10 11 m −1 d −1 with higher salinity. The effects of soluble microbial products (SMP), extracellular polymeric substances (EPS), low molecular-weight (LMW) carbohydrates, sludge particle size and inorganic element accumulation, were evaluated on membrane fouling. Flux recovery of fouled PTFE membranes reached 91.6% with offline cleaning. Overall, results indicate that PTFE hollow fiber AnMBR provides a promising method for the treatment of saline organic wastewater.